Effects of valence and divided attention on cognitive reappraisal processes - Morris, John A. (Soc Cogn Affect Neurosci, 2014)
Numerous studies have investigated the neural substrates supporting cognitive reappraisal, identifying the importance of cognitive control processes implemented by prefrontal cortex (PFC). This study examined how valence and attention affect the processes used for cognitive reappraisal by asking participants to passively view or to cognitively reappraise positive and negative images with full or divided attention. When participants simply viewed these images, results revealed few effects of valence or attention. However, when participants engaged in reappraisal, there was a robust effect of valence, with the reappraisal of negative relative to positive images associated with more widespread activation, including within regions of medial and lateral PFC. There also was an effect of attention, with more lateral PFC recruitment when regulating with full attention and more medial PFC recruitment when regulating with divided attention. Within two regions of medial PFC and one region of ventrolateral PFC, there was an interaction between valence and attention: in these regions, divided attention reduced activity during reappraisal of positive but not negative images. Critically, participants continued to report reappraisal success even during the Divided Attention condition. These results suggest multiple routes to successful cognitive reappraisal, depending upon image valence and the availability of attentional resources.